ADDRESSING EMOTIONAL AND BEHAVIORAL PROBLEMS IN EARLY CHILDHOOD BY USING THE STRENGTH AND DIFFICULTIES QUESTIONNAIRE (SDQ) - Nila Zaimatus Septiana; Palasara Brahmani Laras; Nanda Istoqomah (-, 2023)
Early childhood is a period of amazing development, at this time children experience various kinds of problems, both emotional problems, behavior, and social life related to peers. The main objective of this study was to examine the prevalence of self-reported emotional and behavioral symptoms in a representative sample of parents and early childhood teachers using Goodman's Strengths and Difficulties Questionnaire (SDQ). A total of 110 respondents (teachers and parents) participated. The results showed the prevalence of emotional and behavioral symptoms in the analyzed samples. Some of the problems found from the highest to the lowest are prosocial problems, hyperactivity, problems with peers, emotional problems, and behavioral problems. Based on SDQ items, the highest problems experienced by children are losing their temper 50.4%, reported being easily distracted or having difficulty concentrating 49.6%, and Children were less able to get along better with adults than with other children 56.6%. In conclusion, the SDQ test is offered as a simple and effective tool to propose to all formative agents who are concerned with the interests and concerns of not only early childhood but also adolescents and adults.